PowerShell : automating administrative tasks : learn PowerShell from the inside out, right from the basic scripting all the way to becoming a master at automating, managing and maintaining your Windows environment, a course in three modules /: automating administrative tasks : learn PowerShell from the inside out, right from the basic scripting all the way to becoming a master at automating, managing and maintaining your Windows environment, a course in three modules. ([2017]) - (Solutions architect), Shepard, Michael; Venkatesan, Chendrayan; Talaat, Sherif; Blawat, Brenton J. W
No abstract available